Comminuted Fracture of the Body of the Trapezium and Thumb Carpometacarpal Dislocation: A Particular Pattern - Laura Alonso; José Couceiro (The Surgery Journal, 2018)
Trapezium fractures are uncommon injuries. Our case is that of a thumb carpometacarpal joint dislocation associated to a partly comminuted fracture of the body of the trapezium. To the best of the authors' knowledge, this particular variation has not been previously reported in the indexed literature.